(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
To combat the issue of motorcycle theft in metropolitan areas, researchers have developed a prototype anti-theft device that incorporates biometric locking, vibration detection, SMS, and GPS modules. Using an Arduino Uno microcontroller, the device enhances current security systems by detecting unauthorized movement, allowing only authorized individuals to start the motorcycle, and tracking the owner’s whereabouts in real time. This approach aims to reduce theft and increase recovery opportunities. The prototype is developed using the device’s source code, data analysis, and schematic drawings. The biometric locking system ensures that only authorized users can start the motorcycle. The motorcycle will only start when the user’s registered finger is placed on the fingerprint sensor. The researcher can add the primary fingerprint, and the user can add another afterward. If the vibration sensor detects any illicit movement, this device will produce a buzzing sound to inform anyone around. The GPS and SMS modules offer real-time location monitoring and theft notification by transmitting GPS to the registered number. However, the device cannot send SMS with GPS position where the network satellites are not accessible. The device consumes 3.9478 Ah of power when all components are functional, which is adequate for a standard motorbike battery. This study is about the innovation of an anti-theft system for motorcycles based on Arduino technology, which addresses the limitations of existing systems and enhances the security of the motorcycle. The system has several features, such as biometric-based security, an alarm, SMS, and GPS, and is an upgrade over the previous model that used RF remote. It incorporates biometrics and alarm systems, along with SMS and GPS locator, to prevent motorcycle theft, making it more effective and convenient than the previous prototype, according to feedback from respondents. Keywords: